Pengembangan Media Pembelajaran Operasi Hitung Perkalian Menggunakan Audio Berbasis Podcast Pada Siswa Kelas II Sekolah Dasar - Riska Aprillia; Yudi Yunika Putra; Sisi Pitriyana (Universitas Muhammadiyah Bangka Belitung, 2023)
This research was motivated due to less optimal media use in the learning process, the teachers only used the lecture method, so students were less active in the learning process. Therefore, it is necessary to innovate learning to foster students’ motivation in learning. The purpose of this study was to develop a podcast-based audio on valid and practical multiplication arithmetic operations material for second-grade of elementary school students.This study used Research and Development (R&D) through the 4-D development model from Thiagarajan which consisted of 4 stages such as, (1) define, (2) design, (3) development, and (4) spread (disseminate). Data collection techniques used interviews and questionnaires. Data analysis techniques used descriptive qualitative and quantitative using a Likert scale. The subjects of this research were students in second grade in elementary school which consisted of 32 students. Based on the resulting study the material expert validator obtained a percentage value of 86% (very valid) and the result of media experts was 84.7% (very valid). The results of the small-scale trial with 6 students in the second grade obtained a percentage of 100% (very practical) while the large-scale trial with 26 students in the second grade obtained a percentage of 100% (very practical). So, it can be concluded that the podcast-based audio on the multiplication arithmetic operation material that has been developed is valid and practical as a learning medium and the final product has been distributed to second-grade teachers.